Heterosis and combining ability in a diallel cross of chilli (Capsicum annum L.) - Soh, A. C.; Yap, Thoo Chai; Graham, K. M. (Cambridge University Press, 1976)
In a 7×7 diallel-cross experiment utilizing parents with varying resistance to mosaic virus disease and of different horticultural types significant heterosis over the better parent was found in number of days between sowing and flowering and over the mean of the two parents in other characters. The combining ability analysis revealed that genetic control of most character variation was due to additive effects. It is suggested that pedigree and/or backcross methods are most appropriate for improving this chilli population.